My early life : an illustrated story - Gandhi, M.K (Oxford University Press, 2012)
"Mohandas Karamchand Gandhi's My Early Life (1932) - an adaptation of his authoritative autobiography - is one of the earliest books developed by the Press in India. The charming little book has its own history: at the time Gandhi was in prison, and so was able to devote time to the project being put together by his secretary, Mahadev Desai, in consultation with the Press. This illustrated edition of Mohandas Karamchand Gandhi's My Early Life, specially designed for children and young adults, bears testimony to the classic that continues to sell as a school edition even today. Complemented by contextual notes and including close to 45 evocative line drawings and photos, the book covers the crucial years 1869-1914: from childhood days at home, school life, and teenage desires and confessions to the trip to England and struggles as an attorney, and finally his South African years. This is the story of the flesh-and-blood Mohandas, who finds himself, along with many others, in a particular socio-historical context that sets him off on a life-altering path-towards becoming the Mahatma."--